Mathematics Self-Efficacy Scale Based on Computer - Heru Sukoco; Imam Suharjo (Indonesian Journal of Mathematics Education, 2019)
The results of the PISA (Program for International Student Assessment) survey in 2012-2015 on the achievement of mathematical competencies of Indonesian students showed a significant increase, but the overall achievement was still below the average of the countries belonging to the Organization for Economic Co-operation and Development (OECD). Furthermore, the results of the Trends in International Mathematics and Science Study (TIMSS) report showed that many students like and feel good about mathematics, but their confidence in their mathematical abilities was quite low. Many studies reveal the close association of Mathematics Self-Efficacy (MSE) with the performance/achievement of students' mathematical competencies. In 2015, the PISA survey was done using computerization except in 15 countries, one of them was in Indonesia. Therefore, the results of this study are to produce the first computer-based MSE scale developed in Indonesia.